Cooperativity as quantification and optimization paradigm for nuclear receptor modulators. Issue 9 (26th January 2022) - de Vink, Pim J.; Koops, Auke A.; D'Arrigo, Giulia; Cruciani, Gabriele; Spyrakis, Francesca; Brunsveld, Luc
Abstract : A cooperativity framework describes the formation of nuclear receptor ternary complexes and deconvolutes ligand and cofactor binding into intrinsic affinities and a cooperativity factor, providing a conceptually new understanding of NR modulation. Abstract : Nuclear Receptors (NRs) are highly relevant drug targets, for which small molecule modulation goes beyond a simple ligand/receptor interaction. NR–ligands modulate Protein–Protein Interactions (PPIs) with coregulator proteins. Here we bring forward a cooperativity mechanism for small molecule modulation of NR PPIs, using the Peroxisome Proliferator Activated Receptor γ (PPARγ), which describes NR–ligands as allosteric molecular glues. The cooperativity framework uses a thermodynamic model based on three-body binding events, to dissect and quantify reciprocal effects of NR–coregulator binding ( K ID) and NR–ligand binding ( K IID), jointly recapitulated in the cooperativity factor ( α ) for each specific ternary ligand·NR·coregulator complex formation. These fundamental thermodynamic parameters allow for a conceptually new way of thinking about structure–activity-relationships for NR–ligands and can steer NR modulator discovery and optimization via a completely novel approach.